2023
DOI: 10.1001/jamacardio.2023.3142
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Cardiovascular Imaging

Ramsey M. Wehbe,
Aggelos K. Katsaggelos,
Kristian J. Hammond
et al.

Abstract: ImportanceArtificial intelligence (AI), driven by advances in deep learning (DL), has the potential to reshape the field of cardiovascular imaging (CVI). While DL for CVI is still in its infancy, research is accelerating to aid in the acquisition, processing, and/or interpretation of CVI across various modalities, with several commercial products already in clinical use. It is imperative that cardiovascular imagers are familiar with DL systems, including a basic understanding of how they work, their relative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Several studies have shown how the use of AI Echo can minimize the known limitations of these approaches. 40–42,44,47,50,51…”
Section: Ai Echo For Image Interpretationmentioning
confidence: 99%
“…Several studies have shown how the use of AI Echo can minimize the known limitations of these approaches. 40–42,44,47,50,51…”
Section: Ai Echo For Image Interpretationmentioning
confidence: 99%
“…The authors demonstrated that the system created was more accurate than clinical cardiologists in classifying disease based on echocardiography alone, but further studies are needed to put the system into clinical application [ 86 ]. High-quality prospective evidence is still needed to show how the benefits of DL cardiovascular imaging systems can outweigh the risks [ 242 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Deep learning is a subfield of machine learning that involves the use of artificial neural networks composed of multiple layers of interconnected nodes that are capable of representing complex patterns in data and automatically make predictions without explicit programming [10]. DL has revolutionized various aspects of medicine such as radiology [11], neurology [12], and cardiology [13]. As a promising technique, DL has found its way into the evaluation of histopathological images [14][15][16].…”
Section: Introductionmentioning
confidence: 99%